Study on the influence of secondary aging on the flow behavior and self-healing performance of asphalt mastic - Yu Wang; Yao Zhang; Bo Li; Aihong Kang; Changjiang Kou (Case Studies in Construction Materials)
Asphalt is a kind of high viscosity material with fluidity under certain conditions, which results in the healing function to repair small cracks of asphalt pavement by itself, and thus prolonging the service life of the pavement. With the aging process, the flow behavior of asphalt will gradually deteriorate and synchronously impact the self-healing performance. To gain a deeper understanding of the changes in asphalt's performance characteristics after aging, Fourier transform infrared spectroscopy tests, Frequency scanning tests, and Fatigue-healing-fatigue tests were conducted to examine the changes in flow behavior and self-healing properties of asphalt enduring secondary aging. The results showed that SBS modified asphalt presented superior anti-aging performance compared to base asphalt, since the SBS modifier can effectively prevent the formation of sulfoxides and carbonyl groups in asphalt. However, SBS modifier will also inhibit the flow behavior of asphalt due to its complex three-dimensional spatial structure, leading to a decrease in flow behavior index from 0.967 for unaged base asphalt to 0.672 for SBS modified asphalt, respectively. Furthermore, both of the flow behavior and self-healing performance will be affected by aging process. After secondary aging, the flow behavior index of base and SBS modified asphalt decreased by 9.8 % and 12.1 % compared to the corresponding virgin asphalt mastics, respectively, while the self-healing performance decreasing by 83.9 % and 57.6 %. These findings provide an innovative perspective for secondary recycling research and application of asphalt pavements.